Effects of varied planar dimensions of IPMC on simulated actuation using COMSOL - Danial Haziq, Rizal; Wan Hasbullah, Mohd Isa; Muhammad Amirul, Abdullah; Abdul Majeed, Anwar P. P.; Norasmiza, Mohd (Penerbit UMP, 2023)
This study focuses on mechatronic systems and their use of bending smart materials, specifically the ionic polymer metal composite (IPMC), for compliant actuation. The advantages of IPMC actuators, such as low power consumption and high flexibility, are highlighted. The actuation mechanism of IPMCs involving ion migration, water transport, and mechanical stress imbalance is discussed. The influence of geometric parameters, specifically length and width, on IPMC performance is investigated through simulations. Results show a positive correlation between IPMC lengths exceeding 30 mm and displacement, with longer lengths leading to higher displacements. The relationship between width and maximum displacement is attributed to factors like increased active area, larger polymer volume, and potential effects on mechanical properties. Further electromechanical analysis is needed for a comprehensive understanding of these mechanisms.